2020
DOI: 10.32639/jimmba.v2i4.624
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ukuran Perusahaan Terhadap Audit Delay Dengan Return On Asset Sebagai Variabel Mediasi Pada Sub Sektor Perbankan Tahun 2017-2018

Abstract: Adapun tujuan dari penelitian ini di adakan ialah untuk mengetahui pengaruh ukuran perusahaan terhadap audit delay dengan return on asset sebagai variable mediasi pada sub sektor perbankan tahun 2017-2018. Penelitian ini menggunakan analisis descriptive dengan menggunakan aplikasi SPSS. Adapun sampel diambil dari 15  perusahaan sub sektor perbankan yang terdaftar di BEI pada tahun 2017-2018. Penelitian memanfaatkan Ukuran Perusahaan sebagai variable independen, Audit Delay sebagai variabel dependen serta Retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Hasanah and Enggariyanto's research (2018) revealed that company size is one of the seven factors studied as a determinant of ROA, and it was found from data processing that company size proved to have a significant effect. Further research by Caroline and Hutabarat (2020) with ROA as a variable that mediates between company size and audit delay all results significant that company size has an effect on ROA and ROA affects audit delay. For the next hypothesis that is developed is H2: Company size has an effect on ROA…”
Section: Literature Reviewmentioning
confidence: 90%
“…Hasanah and Enggariyanto's research (2018) revealed that company size is one of the seven factors studied as a determinant of ROA, and it was found from data processing that company size proved to have a significant effect. Further research by Caroline and Hutabarat (2020) with ROA as a variable that mediates between company size and audit delay all results significant that company size has an effect on ROA and ROA affects audit delay. For the next hypothesis that is developed is H2: Company size has an effect on ROA…”
Section: Literature Reviewmentioning
confidence: 90%